Penyuluhan dan Pemenuhan Kelayakan Aspek Hukum BUMDes di Desa Cibitung Kecamatan Ciater Kabupaten Subang - Sri Nurcahyani; Willy Graham Windyanto (Gapenas Publisher, 2022)
Badan Usaha Milik Desa (BUMDes) are business entities that can be useful in helping the economy of rural communities. Cibitung Village, Ciater District, Subang Regency is a village that has promising business potential. The village already has a BUMDes with the name BUMDes Anugerah. However, the BUMDes has been deactivated because the permit has expired. During this period of service, the author conducted counseling on the importance of BUMDes for the village economy. The counseling activity was carried out in the local village hall. After conducting the counseling process, the author advocated with the village community, village government and BUMDes managers to provide assistance regarding the fulfillment of BUMDes permits. Based on the results of the BUMDes Anugerah deliberation, the name was changed to BUM Desa Mekar Sejahtera Cibitung. Then proceed with the preparation of the BUMDes Articles of Association and Bylaws, Making BUMDes TIN, BUMDes Name Decree from the Ministry of Villages, and BUMDes Legal Entity Decree from the Ministry of Law and Human Rights. By doing this activity. Received a positive response from various parties